2004
DOI: 10.1039/b311662j
|View full text |Cite
|
Sign up to set email alerts
|

Organotins in marine mammals and seabirds from Norwegian territory

Abstract: An increasing number of studies indicate that marine mammals and some seabirds are exposed to organotins. However, results from northern and Arctic areas are few. Here results from analysis of tributyltin (TBT), dibutyltin (DBT), monobutyltin (MBT), triphenyltin (TPhT), diphenyltin (DPhT) and monophenyltin (MPhT) in harbour porpoise (Phocoena phocoena), common seal (Phoca vitulina), ringed seal (Phoca hispida) and glaucous gull (Larus hyperboreus) from Norwegian territory are presented. Relatively high concent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
15
0
1

Year Published

2009
2009
2017
2017

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(18 citation statements)
references
References 27 publications
2
15
0
1
Order By: Relevance
“…Lipid results from the present study were also comparable to those from other studies. Lipid percentages in porpoises analysed by Kannan et al (1993), Tanabe et al (1997a) and Berge et al (2004) fall, in general, well in the ranges reported in the present study. Duinker et al (1989) analyzed harbour porpoises from the North Sea between 1977 and 1979 and found percentages ranging from 1.4% to 6.7% for kidney, 5.3-13.9% for brain, 2.1-8.6% for liver, 0.5-7.9% for muscle and 54.2-93.5% for blubber.…”
Section: Distribution Between Tissuessupporting
confidence: 90%
“…Lipid results from the present study were also comparable to those from other studies. Lipid percentages in porpoises analysed by Kannan et al (1993), Tanabe et al (1997a) and Berge et al (2004) fall, in general, well in the ranges reported in the present study. Duinker et al (1989) analyzed harbour porpoises from the North Sea between 1977 and 1979 and found percentages ranging from 1.4% to 6.7% for kidney, 5.3-13.9% for brain, 2.1-8.6% for liver, 0.5-7.9% for muscle and 54.2-93.5% for blubber.…”
Section: Distribution Between Tissuessupporting
confidence: 90%
“…The proportion of DBT to the total BTs in finless porpoises was similar to that observed for common dolphins (60 ± 12%) and minke whales (65 ± 23%) from Korean coastal waters (Choi et al, 2011b). The compositional distribution of BTs in our study was similar to those reported for the livers of porpoises from other countries (Berge et al, 2004;Strand et al, 2005;Nakayama et al, 2009). These findings suggest cetaceans metabolize BT compounds in a similar manner (Lee, 1991;Kannan et al, 1997).…”
Section: Concentration and Composition Of Btssupporting
confidence: 88%
“…To date, several studies have reported the accumulation of BTs and discussed the ecotoxicological implications of this accumulation in whales (Kannan et al, 1997;Kajiwara et al, 2006;Harino et al, 2007Harino et al, , 2008Choi et al, 2011b), dolphins (Kim et al, 1996;Kannan et al, 1997;Tanabe et al, 1998;Choi et al, 2011b), and porpoises (Berge et al, 2004;Ciesielski et al, 2004;Strand et al, 2005;Nakayama et al, 2009). However, little is known about temporal trends of BTs in cetaceans (Strand et al, 2005;Nakayama et al, 2009).…”
Section: Introductionmentioning
confidence: 97%
“…In addition, an especially harmful feature of these compounds is that although they do not significantly bioconcentrate, they are transferred up and accumulate in the food chain to some degree owing to their lipophilic nature (Shawky and Emons 1998). Organic tin compounds are readily incorporated into the tissues of filter-feeding zooplankton, grazing invertebrates, and eventually accumulates in higher organisms such as fish, water birds and mammals (Berge et al 2004;Borghi and Porte 2002;Harino et al 2000;Ohji et al 2007). Several reported physiological effects on invertebrates, such as Dog-whelks (Nucella lapillus) and sea snails (Thais clavigera) exist at environmental conditions of a few ng/l (Gibbs and Bryan 1986;Horiguchi et al 1997), as well as effects, especially on the immune defence system, of fish and seals (Allner et al 2010;Frouin et al 2008).…”
Section: Introductionmentioning
confidence: 99%